TRI SENTRA PENDIDIKAN : STRATEGI MENINGKATKAN KEMAMPUAN ANAK DALAM BELAJAR - Mei Manullang; Syahrial (STKIP Subang, 2026)
Children’s education is a holistic process that involves multiple learning environments, not only schools but also families and communities. The concept of Tri Sentra Pendidikan emphasizes that these three environments play complementary roles in supporting the development of children’s learning abilities. This study aims to analyze the roles and synergy of Tri Sentra Pendidikan in enhancing children’s learning abilities based on a literature review. The research employed a qualitative method with a library research approach by reviewing and analyzing relevant books and scholarly journal articles. Data were analyzed using a descriptive-analytical technique to identify the role so ffamily, school, and community in supporting children’s learning abilities. The findings indicate that the family serves as the primary foundation in shaping children’s learning habits and motivation, schools function to develop academic abilities and character through structured learning, and communities act as supportive environments that enrich children’s learning experiences through social interaction and cultural values. The harmonious synergy among these three educational centers is proven to create a conducive and sustainable learning environment, thereby supporting the optimal development of children’s learning abilities. Therefore, the integrated implementation of Tri Sentra Pendidikan is an essential strategy for improving the quality of learning and children’s overall development.